Kajian pengelolaan sampah rumah tangga (SRT) dan sampah sejenis sampah rumah tangga (SSRT)) di Kabupaten Teluk Bintuni - Nicolas Riruma; Nurhaida Sinaga; Marlyn N. Lekitoo (Cassowary, 2021)
The objectives to be achieved from this research are to determine the amount of waste generation and characteristics, evaluate waste management in 2019, project a waste balance for 2020-2025, and identify the form of waste management policies, strategies and programs for 2020-2025 in Teluk Bintuni Regency. The results of the study, the amount of waste generation was 3.46 l / o / h; composition of organic waste 67.12%, plastic waste 26.30%, and other inorganic waste 6.75%; managed waste 65.55%; served population 76.90%; implementation of operational technical standards 45.43%; effectiveness of the role of local government 39.49% (less effective criteria); low community behavior in waste management (69%), community perception in good waste management (81%); projected waste balance for 2020-2025 waste generation 169,229.79 tons, 30% reduction target (44,427 tonnes), 70% handling target (122,596 tonnes), 100% managed waste by 2025 (169,229.79 tonnes); 2 forms of policies, 6 strategies and 17 waste management programs were identified for 2020-2025.